Utilizing Task-Based Learning Ac Utilizing Task-Based Learning Activities to Enhance Students’ English Workplace Communication Skills - Sucharitrak , Suphatra; Sucharitrak, Phornsak (วารสารนวัตกรรมการจัดการศึกษาและการวิจัย, 2026)
Abstract Workplace communication in English is a common pain point for Thai university graduates when transitioning to office-based careers. The study aimed to (1) develop and test instructional materials utilizing task-based activities for workplace communication, (2) determine whether the instructional materials improve students’ workplace communication skills, and (3) explore students’ reactions towards the instructional materials. The study was conducted with 35 students who enrolled in the English for Office Management course. The entire instructional material covered 15 weeks, comprising 45 hours of normal classroom learning. The instructional package included a pre-test and post-test of vocabulary knowledge and workplace communicative role play tasks. The students’ ’learning logs’ indicated learning gain in workplace vocabulary, their preferences for learning tasks, and also their challenges. Thirty-five students who participated in role-play tasks and performed the pre-test and post-test were analyzed to observe the evidence of improvement. This study shows that the positive effect is on learning tasks, which are structured lesson units that enable students to greatly improve their scores from pre-test to post-test in the development of students’ speaking performance for workplace contexts. The results indicated that instructional materials with task-based activities in workplace communication were appropriate for real workplace situations and could be used to develop the students’ practical communication skills needed in their future work.